What women emphasise as important aspects of care in childbirth – an online survey. (10th October 2021) - Vedeler, C; Nilsen, ABV; Blix, E; Downe, S; Eri, TS
Abstract : Objective: To explore and describe what women who have given birth in Norway emphasise as important aspects of care during childbirth. Design: The study is based on data from the Babies Born Better online survey, version 2. Setting: The maternity care system in Norway. Study population: Women who gave birth in Norway between 2013 and 2018. Method: Descriptive statistics were used to describe sample characteristics and to compare data from the B3 survey with national data from the Medical Birth Registry of Norway. The open‐ended questions were analysed with an inductive thematic analysis. Main outcome measures: Themes developed from two open‐ended questions. Results: The final sample included 8401 women. There were no obvious differences between the sample population and the national population with respect to maternal age, marital status, parity, mode of birth and place of birth, except for the proportion of planned home births. Four themes and one overarching theme were identified; Compassionate and Respectful Care, A Family Focus, Sense of Continuity and Consistency, and Sense of Security. Overarching theme: Coherence in Childbearing. Conclusions: Norwegian women across all birth settings emphasise maternity care that authentically focuses on both socio‐cultural and psychological aspects of care, and physical and clinical factors. If the positive aspects of care identified in this study are adopted at all levels of the maternity care system and from all care providers, there is a high chance that most women will have a safe outcome, and a strong sense of coherence related to a positive birth and motherhood experience. Tweetable abstract: Having a baby is a pivotal life changing experience and not just a clinical event, according to a survey of 8400 women in Norway. Positive birth and motherhood experiences depend on maternity staff who are both skilled and kind. Tweetable abstract: Having a baby is a pivotal life‐changing experience and not just a clinical event, according to a survey of 8400 women in Norway. Positive birth and motherhood experiences depend on maternity staff who are both skilled and kind.